Evaluation of Risk Factors for Occurrence of Bronchopulmonary Aspergillosis in Pediatric Patients with Cystic Fibrosis at a Tertiary Care Hospital - Yogesh Hareshbhai Bhadani (Asian Journal of Clinical Pediatrics and Neonatology, 2017)
Background: Allergic bronchopulmonary aspergillosis (ABPA) represents a significant complication in individuals of all ages with cystic fibrosis (CF), with prevalence rates ranging from 6% to 25%. Hence; the present study was conducted to evaluate risk factors for occurrence of bronchopulmonary aspergillosis in pediatric patients with cystic fibrosis at a tertiary care hospital. Materials & Methods: A study was conducted on 50 pediatric patients with cystic fibrosis, gathering comprehensive demographic and clinical data. Patients underwent various evaluations, including clinical assessment, spirometry, chest radiography, sputum analysis, and tests for Aspergillus sensitization, such as IgE levels and skin prick testing. The results were recorded and analyzed to identify risk factors associated with Aspergillus sensitization in cystic fibrosis patients. Results: A study of 50 pediatric subjects with cystic fibrosis (CF) found that 80% had abnormal chest radiographic findings and 20% had allergic bronchopulmonary aspergillosis (ABPA). ABPA was more common in patients with low CF scores, age over 12, atopy, and eosinophilia. Patients with ABPA tended to have lower lung function, as measured by FEV1 and FVC. The study's mean subject age was 41.3 months, with 66% being boys and a mean BMI of 13.3 kg/m2. Conclusion: CF is an autosomal recessive life-limiting multisystem disorder. ABPA is a pulmonary disorder that often occurs in patients with asthma or CF. CF patients with ABPA should undergo regular follow-up.